Introduction to islamic law - Seminario Hurtado, Nuccia (2019)
The purpose of this article is to analyze the fundamentals and sources of Islamic law, based on the study of the history of Islam and its prophet Muhammad, and also demonstrate the reasons why it is considered a religious right.